2019
DOI: 10.3390/met9080914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rise and Fall Time on Dwell Fatigue Behavior of a High Strength Titanium Alloy

Abstract: Frequency is an important factor influencing the fatigue behavior. Regarding to the dwell fatigue, it corresponds to the effect of rise and fall time, which is also an important issue especially for the safety evaluation of structure parts under dwell fatigue loading, such as the engines of aircrafts and the pressure hulls of deep-sea submersibles. In this paper, the effect of rise and fall time (2 s, 20 s, 110 s, and 200 s) on the dwell fatigue behavior is investigated for a high strength titanium alloy Ti-6A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, many results have shown that the dwell of the maximum stress could greatly reduce the fatigue life of titanium alloys [8][9][10] and the dwell fatigue of titanium alloys often presents the feature of cleavage or quasi-cleavage facets in the crack initiation region [1,11,12]. The results for the titanium alloy Ti-6Al-2Sn-2Zr-3Mo-X indicated that the rise and fall time significantly affects the dwell fatigue life, and the dwell fatigue life with the rise and fall time could be correlated by a linear relation in log-log scale [13]. For the dwell fatigue of Ti-6Al-4V ELI alloy, it has been shown that the stress ratio has great influence on the dwell fatigue life and dwell fatigue failure mode [14].…”
Section: Introductionmentioning
confidence: 98%
“…For example, many results have shown that the dwell of the maximum stress could greatly reduce the fatigue life of titanium alloys [8][9][10] and the dwell fatigue of titanium alloys often presents the feature of cleavage or quasi-cleavage facets in the crack initiation region [1,11,12]. The results for the titanium alloy Ti-6Al-2Sn-2Zr-3Mo-X indicated that the rise and fall time significantly affects the dwell fatigue life, and the dwell fatigue life with the rise and fall time could be correlated by a linear relation in log-log scale [13]. For the dwell fatigue of Ti-6Al-4V ELI alloy, it has been shown that the stress ratio has great influence on the dwell fatigue life and dwell fatigue failure mode [14].…”
Section: Introductionmentioning
confidence: 98%